A REDESAIN TRACER REKAM MEDIS DI PUSKESMAS BONTANG UTARA II KOTA BONTANG: REDESIGN TRACER MEDICAL RECORDS AT PUBLIC HEALTH CENTER BONTANG UTARA II BONTANG CITY) - Husin, Husin; Ningsih, Eka Rahma; Syahrul, Syahrul; Bar, Abdul (Sekretariat Program Studi Sarjana Terapan Manajemen Informasi Kesehatan Politeknik Indonusa Surakarta., 2023)
Tracer is one of the important facilities in unit filling. A good tracer has strong materials, the size of the tracer is adjusted to the medical record map, the tracer has an attractive and practical shape when used and the tracer has a contrasting/striking color. The purpose of this study was to produce a new tracer design design at the North Bontang Health Center II Bontang City based on physical aspects, anatomical aspects and content aspects. Research used is Research and Development (R&D). This study has a single variable, namely the redesign of the new Medical Record tracer. The result of this study is the selection of alternative design I, the selection of alternative tracer designs based on feasibility, namely using the assessment rubric then the total respondent values are calculated using the median formula. Alternative tracer design material using PVC (poly vhynil chloride), size which is 29.7 cm long and 13.9 cm wide, combination of green and white colors, Tracer design has a complete anatomy, namely there is a title, logo and name of the institution/government, tracer content items include date, medical record number, patient name, destination poly and borrower.